URGENSI STRATEGI DALAM PENGEMBANGAN KOMPETENSI PUSTAKAWAN SEBAGAI UPAYA PENINGKATAN KINERJA PERPUSTAKAAN - Wiji Suwarno (Central Library of Universitas Sebelas Maret, 2016)
Progressi of the library depend on the librarian as the mean manager, where the selfquality of librarians become the foundation progress. While the self quality of librarianshas competences. This article talks about the potential of librarian competence whichis possible to developed. The conclusion of this article is librarian have to improve hisor her performance in the realm of motive, trait, self concept, and kowledge. Whilethe urgency point strategy on the development of HR competencies are to secureunderstanding, to establish acceptance, to motive action, to achieve the goal.